Rethinking Graduate Employability in Context Discourse, Policy and Practice - Siivonen, Päivi; Isopahkala-Bouret, Ulpukka; Tomlinson, Michael; Korhonen, Maija; Haltia, Nina (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This open access book offers critical, multidisciplinary analyses on graduate employability. The book examines employability at the macro, meso and micro levels: higher education policy, the labour market, higher education institutions, organisations, individuals and social groups, in European, North American and Australian contexts. The contributors provide social and contextual analysis of graduate employability as a theoretical concept, a discourse and policy imperative and a social and discursive practice. The volume also introduces novel methodological perspectives to study the process of graduate employability. There is an urgent need for comprehensive and unified critical perspectives on graduate employability, as such analyses have so far been scarce and often isolated. Besides filling this gap in the literature, the book will also serve as essential reading on courses that focus on graduate careers and employability as well as higher education policy and practice. Päivi Siivonen is Associate Professor in the Department of Education, University of Turku, Finland. Ulpukka Isopahkala-Bouret is Professor in the Department of Education, University of Turku, Finland. Michael Tomlinson is Professor in the Southampton Education School, University of Southampton, UK. Maija Korhonen is University Lecturer at the Educational Sciences and Psychology, University of Eastern Finland. Nina Haltia is Senior Researcher in the Department of Education, University of Turku, Finland.